2008
DOI: 10.1590/s1807-59322008000600017
|View full text |Cite
|
Sign up to set email alerts
|

Ginger Extract (Zingiber Officinale) has Anti-Cancer and Anti-Inflammatory Effects on Ethionine-Induced Hepatoma Rats

Abstract: Habib SHM, Makpol S, Hamid NAA, Das S, Ngah WZW, Yusof YAM. Ginger extract (zingiber officinale) has anti-cancer and anti-inflammatory effects on ethionine-induced hepatoma rats. Clinics. 2008;63:807-13. OBJECTIVE:To evaluate the effect of ginger extract on the expression of NFκB and TNF-α in liver cancer-induced rats. METHODS: Male Wistar rats were randomly divided into 5 groups based on diet: i) control (given normal rat chow), ii) olive oil, iii) ginger extract (100mg/kg body weight), iv) choline-deficient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
148
0
5

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 236 publications
(159 citation statements)
references
References 28 publications
6
148
0
5
Order By: Relevance
“…We have previously demonstrated that ginger extract inhibited the growth of HepG2 hepatoma cells and the formation of tumor in liver cancer-induced rats (Mohd Yusof et al, 2008). Ginger was believed to suppress the hepatocarcinogenesis mainly through induction of apoptosis in the cancer cell, as indicated by downregulation of anti-apoptotic Bcl-2 protein and upregulation of pro-apoptotic protein caspase-8 (Mohd Yusof et al, 2008), as well as supressing inflammation (Jeong et al, 2009;Sang et al, 2009) by inactivating nuclear factor-kappa beta (NF-κβ) (Habib et al, 2008). Other studies have also reported the mechanism of anti-tumour effect of ginger extract via induction of apoptosis in various human cancer cell lines following treatment with ginger phenolic compounds (Lee and Surh, 1998;Miyoshi et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously demonstrated that ginger extract inhibited the growth of HepG2 hepatoma cells and the formation of tumor in liver cancer-induced rats (Mohd Yusof et al, 2008). Ginger was believed to suppress the hepatocarcinogenesis mainly through induction of apoptosis in the cancer cell, as indicated by downregulation of anti-apoptotic Bcl-2 protein and upregulation of pro-apoptotic protein caspase-8 (Mohd Yusof et al, 2008), as well as supressing inflammation (Jeong et al, 2009;Sang et al, 2009) by inactivating nuclear factor-kappa beta (NF-κβ) (Habib et al, 2008). Other studies have also reported the mechanism of anti-tumour effect of ginger extract via induction of apoptosis in various human cancer cell lines following treatment with ginger phenolic compounds (Lee and Surh, 1998;Miyoshi et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…For centuries, it has been used as food flavoring agent as well as for traditional medicinal purposes (Ali et al, 2008). Current trend in research has focused its attention to ginger given its anti-cancer, anti-oxidant, and anti-inflammatory properties (Masuda et al, 2004;Grzanna et al, 2005;Shukla and Singh, 2007;Habib et al, 2008). Recently, our laboratory has demonstrated anti-tumor effects of ginger extracts against colon cancer cell lines through the induction of apoptotic pathway coupled with cell cycle arrest at G 0 /G 1 phase (Abdullah et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Zingiber officinale, commonly known as ginger, is traditionally used as a spice in various foods and beverages in a wide variety of ailments such as; asthma, diabetes, nausea and pain (Afshari et al, 2007). Also, Habib et al (2008) reported that ginger might act as an anti-inflammatory and anti-cancer (Habib et al, 2008). The dried rhizomes of ginger (rich in pungent phenolic compounds: gingerols and shogaols) or extracts thereof are important ingredients of many traditional/ alternative medicines worldwide (Ling et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Liver cancer, scientifically known as hepatocellular carcinoma, is one of the five most common cancers in the world, and is caused by chronic consumption of hepatotoxins and infection by the hepatitis B viruses [27]. Scientific studies carried out in the recent past have shown that ginger possess chemopreventive properties, and was effective in preventing ethionine-induced [28,29], and DEN-initiated and CCl 4 -promoted hepatocarcinogenesis in rats [30].…”
Section: Ginger Prevents Chemical-induced Liver Cancermentioning
confidence: 99%